AB0230 STATINS TO PREVENT RHEUMATOID ARTHRITIS: INCONCLUSIVE RESULTS OF THE STAPRA TRIAL. (13th June 2020) - Van Boheemen, L.; Turk, S. A.; Van Beers - Tas, M. H.; Bos, W. H.; Marsman, D.; Griep, E. N.; Starmans, M.; Popa, C. D.; Van Sijl, A. M.; Boers, M.; Nurmohamed, M.; Van Schaardenburg, D.
Abstract : Background: Persons at high risk for developing rheumatoid arthritis (RA) may benefit from a low-risk pharmacological intervention aimed at primary prevention. Statins are safe and widely-used drugs; previous studies demonstrated disease-modifying effects of statins in RA patients 1 as well as an association between statin use and a decreased risk of RA development 2 . Objectives: We designed a multi-center, randomized, double-blind, placebo-controlled trial to investigate if atorvastatin use for 3 years could prevent arthritis. Methods: Persons at high risk for RA, defined by the presence of arthralgia and anti-citrullinated protein antibody (ACPA) concentration >3xULN or both ACPA and rheumatoid factor (RF), were randomized to atorvastatin 40 mg daily or placebo for 3 years. Eligible participants were ≥18 years, had no indication for lipid-lowering therapy and had no clinical synovitis. The primary endpoint was development of clinical arthritis. Our goal was to include 220 patients, based on an anticipated 30% risk reduction by atorvastatin. Analysis was by intention-to-treat. Results: 189 patients were screened, 175 were eligible, but only 67 persons were included of whom 62 were randomized (figure 1 ). The main reason for non-inclusion was unwillingness to use study medication (n=58, 54%). Inclusion was stopped after 38 months due to the low inclusion rate. Analyses were performed 1 year after inclusion stop. Mean follow up was 18 (0-36) months. Mean age was 48 years and 74% of participants were female. 14 persons (23%) developed clinical arthritis: 8/31 (26%) in the atorvastatin group and 6/31 (19%) in the placebo group (HR 0.8, 95% CI 0.3-2.2) after a median period of 7.5 (IQR 5.3-21.8) months (atorvastatin) and 4 (0-14.8) months (placebo). In the atorvastatin group, 17 persons completed the study according to protocol, 6 dropped out and 8 continued follow-up after prematurely stopping study medication. In the placebo group, 16 persons completed the study according to protocol, 11 dropped out and 4 continued follow-up after prematurely stopping study medication. Median duration of study medication use was 9 (6-26) months (atorvastatin group) and 8 (3-17) months (placebo group). Conclusion: The results of this trial are inconclusive due to severe difficulties with patient inclusion and low treatment adherence. The difficulty to enter and retain participants in this prevention trial is highly relevant given the current interest in treating RA in an ever earlier phase. At-risk individuals' perceptions should be taken into account when designing preventive trials and will be important in optimizing acceptance and adherence to preventive treatment. Currently we are finalizing research into the motivation and barriers for participation in different primary prevention trials of RA and the willingness to initiate different types of preventive treatment in individuals in the at-risk phase of RA. References: [1]McCary et al. Lancet. 2004; 19;363(9426):2015-21 [2]Chodick G et al. PLoS Med. 2010;7(9):e1000336 Disclosure of Interests: Laurette van Boheemen: None declared, S.A. Turk: None declared, M.H. van Beers - Tas: None declared, W.H. Bos Grant/research support from: abbvie, sanofi, roche, celgene, ucb, novartis, Speakers bureau: abbvie, Sanofi, eli lilly, Diane Marsman: None declared, E.N. Griep: None declared, M. Starmans: None declared, C.D. Popa: None declared, A.M. van Sijl: None declared, Maarten Boers: None declared, Michael Nurmohamed Grant/research support from: Not related to this research, Consultant of: Not related to this research, Speakers bureau: Not related to this research, Dirkjan van Schaardenburg: None declared